Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Pada Coffee Shop Janji Jiwa - Vira Aurellia; Ria Marginingsih (CV. KAMPUS AKADEMIK PUBLISING, 2024)
With the progress in economic and technological fields and the rise in global market competition, businesses are working to deliver products and services that better meet customer needs while offering competitive prices. This endeavor aims to attract new customers and retain existing ones. This study examines the effects of service quality, product quality, and pricing on customer satisfaction. The focus is on the customers of Discussion Coffee. The study employs purposive sampling, which involves selecting samples based on specific criteria. Multiple linear regression analysis is the method used for analysis. The results show that the variables in this research model—service quality, product quality, and pricing—all have a significant and positive impact on customer satisfaction at Discussion Coffee in Tambun. These findings indicate that enhancements in service quality, product quality, and pricing lead to higher customer satisfaction.